Medicinal value of Ginger (Zingiber officinale) in Jaffna - Krishnapillai, N. (My University, 2005)
Ginger is used as a flavoring agent and a medicinal plant by more than 90% of people in Jaffna. It is cultivated in home gardens and in vegetable gardens. Ginger production in Jaffna is very low and it yields pale yellow colored small rhizomes with good flavor, aroma and taste. People in Jaffna drink ginger tea to prevent cough, fever and indigestion. During puberty and after childbirth women are fed with fresh or dried ginger, although 50% of the young girls do not know the medicinal value of ginger. Moisture content, pH, total soluble solids, and peel/edible portion ratio of ginger rhizome grown in Jaffna were 78.71%, 6.6, 5.05% and 0.12 respectively. The growth inhibition of 1mL ginger juice on the fungi species Fusarium, Colletotrichum and Curvularia were 7%, 71% and 64.2% respectively.
Keywords: Antifungal activity; Cough; Fever; Ginger tea; Indigestion